Analysis of financial statements to assess financial performance in savings and loan cooperatives CV. Maju Bersama Perdagangan in Simalungun Regency - Sari Bulan Tambunan (Institute of Computer Science (IOCS), 2023)
This study aims to describe the financial performance of cooperative savings and loans CV. Maju Bersama Perdagangan in Simalungun Regency for the 2011–2018 period, find out the dominant factors that have caused the decline in the financial performance of the savings and loan cooperative CV. Maju Bersama. This research was conducted using qualitative descriptive analysis methods and inductive descriptive analysis. The object of research is the Savings and Loans Cooperative CV. Maju Bersama. Moving Forward Together with Perdagangan in Simalungun Regency The results of this study show that the value of the cash ratio, debt to asset ratio, and total asset turnover tend to increase and are in good condition. The profitability value of own capital tends to decrease and is not in good condition. To increase the value of liquidity, cooperative management should increase collection on receivables. To increase the value of solvency, cooperative management should maintain its financial condition by paying debts while maximizing the use of assets. To increase the value of activities, cooperative management should provide and increase sales of assets owned, namely cash and cash equivalents, in order to optimize effectiveness and produce residual business results. To increase the profitability of own capital, cooperative management should increase sales ability, followed by cost management to generate profits, in order to increase profitability for the coming period.